2017
DOI: 10.1080/13504851.2017.1355537
|View full text |Cite
|
Sign up to set email alerts
|

Long-run expectations in a learning-to-forecast experiment

Abstract: In this paper, we elicit both short and long-run expectations about the evolution of the price of a financial asset by conducting a Learning-to-Forecast Experiment (LtFE) in which subjects, in each period, forecast the the asset price for each one of the remaining periods. The aim of this paper is twofold: on the one hand, we try to fill the gap in the experimental literature of LtFEs where great effort has been made in investigating short-run expectations, i.e. one step-ahead predictions, while there are no c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…When agents learn from their past errors, and adopt correction mechanisms to account for past deviations of their forecasts from correct values, market oscillations can be dampened, i.e., fat tails of returns PDFs can be reduced. The rationale of such an evidence is that, apart from the purely theoretical hypothesis of always-perfectly informed agents, an adaptive correction scheme reveals to be very useful from the aggregate point of view, as confirmed by experiments done in related literature (see Colasante et al (2017Colasante et al ( , 2018 and Anufriev et al (2013), among others).…”
Section: Conclusive Remarksmentioning
confidence: 91%
See 1 more Smart Citation
“…When agents learn from their past errors, and adopt correction mechanisms to account for past deviations of their forecasts from correct values, market oscillations can be dampened, i.e., fat tails of returns PDFs can be reduced. The rationale of such an evidence is that, apart from the purely theoretical hypothesis of always-perfectly informed agents, an adaptive correction scheme reveals to be very useful from the aggregate point of view, as confirmed by experiments done in related literature (see Colasante et al (2017Colasante et al ( , 2018 and Anufriev et al (2013), among others).…”
Section: Conclusive Remarksmentioning
confidence: 91%
“…A broader approach is used by Aliabadi et al (2017), who show how agents' behavior varies according to the combined effect of individual risk attributes and to learning abilities to account for errors done in past predictions. Other recent contributions show the impact of self-correcting behavior on long-run expectations, as in Colasante et al (2018). In Colasante et al (2017) an experiment is shown to report that agents use adaptive expectations instead of rational ones and that this may lead to a form of collective rationality (despite the absence of communication among participants), which consists in a robust divergence of predictions from the fundamental value.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the experimental results in LtFEs, especially in the one step-ahead predictions, subjects predict the next price anchoring their predictions around the last realized price. A similar mechanism holds for the long-run predictions, as shown in Colasante et al [2016]. The alternative algorithm proposed in this paper, called the Exploration-Exploitation Algorithm, is based on the empirical as well as experimental evidence that agents anchor their expectations around the last market price conditioning the range of variability of expectations on the past observed price volatility.…”
Section: Introductionmentioning
confidence: 90%
“…to submit forecasts narrowly centred in p t−1 . This is particularly true for the one-step-ahead predictions for which subjects receive an immediate feedback Colasante et al [2016].…”
Section: The Exploration-exploitation Algorithmmentioning
confidence: 99%
See 1 more Smart Citation